Sleeping through aging: telomere dynamics and longevity in Glis glis - Wright, Kristen, author; Swygert, Sarah, advisor; Shavlik, Michael, committee member (Colorado State University. Libraries, 2026)
Telomeres are the important repetitive DNA sequences at the end of chromosomes that help them maintain their structure and stability. As cells divide, telomeres may become shortened as they prevent damage to the chromosome, and can help in determining cellular lifespans. While telomere shortening has been well documented within humans, there are other species with telomere dynamics which are less explored. Namely, the European Edible Dormouse (Glis glis) demonstrates an atypical lengthening of telomeres in old age, contradictory to the trend seen in humans and many other species. The mechanisms and causes behind this have remained poorly understood and underexplored. With a focus on Glis glis, this literature review examines both the lifestyles of edible dormice and their observed telomere dynamics, provided within the context of broader cross-species telomere regulation. Across literature, one behavior which seems to be key to this unique dynamic in dormice is their torpor. Food availability, time spent in euthermy, and telomerase activity are all influenced by torpor, and in turn, affect telomere regeneration. Alternative methods of telomere lengthening and maintenance are also explored, highlighting a complex metabolic relationship between the multiple factors resulting in the observed telomere lengthening seen in dormice. Developing our understanding of this unique characteristic provides an opportunity to uncover new mechanisms behind telomere maintenance within a species that challenges traditional models of aging.
Keywords: telomere; torpor; edible dormouse